Chordal graphs through clique trees - Gutierrez, Marisa; Tondato, Silvia (Cadernos do IME - Série Informática, 2022)
Here we present a part of the work in collaboration with Jayme Luiz Szwarcfiter and Marisa Gutierrez, during the development of the thesis of Silvia Tondato at Facultad de Ciencias Exactas (UNLP), "Grafos Cordales: árboles cliques y representaciones canónicas’’, finished in 2009.